La difusión de las ideas de John Dewey en el Paraguay por Ramón Indalecio Cardozo - García, José E. (2024)
The American John Dewey and the Paraguayan Ramón Indalecio Cardozo are two outstanding representatives in the field of education in the first half of the 20th century, in their respective countries. Likewise, both devoted their attention to psychology, due to the interest that it arouses in itself, or as an instrument to strengthen their approaches to the field of pedagogy. Dewey produced one of the first Psychology texts published in his country and theorized about the nature of the reflex arc, establishing the conceptual foundations of functionalism. Cardozo fostered the applications of psychology in the field of school education, introduced the ideas of some of the most influential authors of his time to Paraguay, and promoted the use of the first psychometric tests. The work lines of both authors met in 1923, with the presentation of Dewey’s ideas by Cardozo, in an article published in 1923, now a century ago. The purpose of this paper is to review the reception of Dewey’s ideas in Paraguay by Cardozo, to analyze the discusión that the Paraguayan author made about his American counterpart, and to evaluate the impact of Dewey’s ideas on the work of Cardozo and the diffusion of the active School in Paraguay. The article is of a historical and argumentative nature and is supported by a review of the primary and secondary sources that are relevant to the understanding and study of the subject matter. At the same time, it seeks to be a contribution to psychological literature on the first century of the first diffusion of John Dewey’s pedagogical and psychological ideas in Paraguay.